Morphological and Agronomic Performance of Some Maize (Zea mays L.) Hybrids in the Agro-ecological Conditions of North-East Benin. - AGBIDINOUKOUN, ARNAUD (My University, 2022)
Background and Objective: Maize ( Zea mays L.) plays an important role in food security in Benin. However, its production is constrained by several factors, which constitute a threat to the food security and annual income of smallholder farmers. The objective of this study was to evaluate the agro-morphological performance of maize varieties in Northeastern Benin. Materials and Methods: Sixteen maize varieties, including fifteen hybrids and one composite variety, were evaluated in three experimental sites, Komkoma, Ina and Angaradébou. Thirteen agro-morphological traits and seven quantitative and six qualitative variables were studied. Results: Significant differences were observed among the hybrids for the different agro-morphological traits. The ascending hierarchical classification (HAC) revealed that this variability is structured in three genotypical clusters. Clusters 1 and 3 included respectively hybrids with intermediate and late vegetative cycles, more productive with medium size plants. Conclusion: Two promising hybrids belonging to genotypic clusters 2 and 3 were identified. These are all late-cycle hybrids (M1026-4 and M1026-7). These results can be directly used for a programme of dissemination and diffusion of resilient maize varieties in Northeast Benin, particularly in agricultural development clusters 2 and 4.
Keywords: Cereal crops; adaptation; food security; promising hybrids; disease severity; genotype×environment interaction